A reassessment of bunodont metatherians from the paleogene of itaboraí (Brazil): systematics and age of the Itaboraian salma - Oliveira, Édison V. (2011)
Early Paleogene metatherians with inflated, low cusps (bunodont dentition), such as Bobbschaefferia, Procaroloameghinia, Protodidelphis, Guggenheimia, and Zeusdelphys have been subject to different interpretations regarding their affinities. A phylogenetic study including these bunodont marsupials and other selected metatherians presented here leads to the recognition of the following taxonomic assignments: "Ameridelphia", Protodidelphidae: Carolocoutoia ferigoloi, Guggenheimia brasiliensis, G. crocheti sp. nov., Protodidelphis vanzolinii, P. mastodontoides (=Robertbutleria mastodontoidea), Periprotodidelphis bergqvisti gen. et sp. nov., and Zeusdelphys complicatus; Marsupialia, Didelphimorphia, Peradectoidea, Caroloameghiniidae: Procaroloameghinia pricei; Australidelphia, Polydolopimorphia, family indet.: Bobbschaefferia fluminensis and aff. Bobbschaefferia sp. The phylogenetic analysis does not support a closer relationship between protodidelphids and living didelphids as well as between Guggenheimia and Mirandatherium. No closer relationship was found between Zeusdelphys with Minusculodelphis and Monodelphopsis. Procaroloameghinia is regarded as a peradectoid didelphimorphian with bunoid dentition convergent with, but without direct affinities to, protodidelphids or polydolopimorphians. Bobbschaefferia is regarded as a basal polydolopimorphian, even though the scarce evidence at hand prevents us from assign it to any particular family of the suborder Hatcheriformes. Correlation with stratigraphic, sedimentary and magmatic data from some of the best studied margin basins in SE Brazil, together with the systematic reassessment of bunodont metatherians from Itaboraí, suggest that the Itaboraian SALMA is latest Paleoceneearly Eocene in age. Itaboraian protodidelphids, sternbergiids and caroloameghiniids are also recorded in the Las Flores locality/ Formation (central Patagonia) and in the La Barda locality (northwestern Patagonia) during the latest Paleocene and early Eocene.